Respons Stres Sapi Bali Jantan pada Proses Pengangkutan dan Pemuatan ke Atas Kapal Ternak (STRESS RESPONSE OF BALI BULLS DURING TRANSPORTATION AND LOADING PROCCESS ONTO THE CATTLE SHIP) - Widayati, Sri; Astuti, Puji; Widiyono, Irkham (Jurnal Veteriner, 2019)
Transportation is needed for livestock distribution from production centers to consumption centers. This might potentially result in a stressful condition for the cattle. The study was aimed to observe the stress response of Bali bulls during the transport and loading proccess onto the ship. Six adult clinically healthy Bali bulls were used in this study. The animals were housed in pen at the animal quarantine installation, given dried straw and drinking water ad libitum since three days before the study. The animals were loaded on the truck in 30 minutes, transported to the harbor in 15 minutes, and loaded on to the ship in 30 minutes. On the ship the animals were kept in a pen bedded with straw and given dried straw and drinking water ad libitum for 19 hours. Venous blood samples were collected from jugular vein during the rest in pen before loading on to the truck, after loading on the ship, and about 19 hours after loading and resting in the ship pen. Serum was separated by centrifugation and stored at -20oC for cortisol analysis. The concentrations of cortisol was analyzed by using enzyme linked immunosorbent assay (ELISA). The results showed that the average of serum cortisol concentration of Bali bulls was at the level of 33.81±28.52 ng/mL in the rest period at the quarantine installation, increased significantly to the level of 138.41±102.57 ng/mL after loading onto the ship (P<0.05), and decreased again to the level of 41.54±43.47 ng/mL after 19 hours of resting period in the pen on the ship (P>0.05). It can be concluded that Bali bulls may suffer from stress during transport and loading proccess which can be recovered after resting in the ship pen.